Library Cooperation In Collection Development Effort In Library At State Of Islamic High School Mandailing Natal - Fatimah; Azhar, Anang Anas; Purwaningtyas, Franindya (International Journal of Cultural and Social Science, 2022)
This research discusses about Library Cooperation in Efforts to Develop Collections at the Library of the State Islamic High School (STAIN) Mandailing Natal. This study aims to find out how library collaboration is in an effort to develop collections at the State Islamic High School Library (STAIN) Mandailing Natal. This study uses a qualitative descriptive approach. Collecting data using interviews, observation and documentation techniques. Data analysis techniques through three stages, namely, data reduction, presentation and drawing conclusions. The results of this study indicate that 1. The Mandailing Natal STAIN Library in an effort to develop collections has collaborated with several agencies such as the BI Corner, and the National Library of Indonesia. 2. The follow-up to the collaboration between the library and the BI Corner has been well realized, both parties have benefited, the STAIN Mandailing Natal Library has benefited from the collaboration, namely the reading corner and 175 book titles and 215 copies, BI Corner as a means of promotion and socialization to the public about Bank Indonesia. Several electronic journals from the National Library of Indonesia, while the National Library of Indonesia has not received feedback from the STAIN Library. 3. In collaborating, the STAIN Mandailing Natal Library experienced many obstacles, namely in the field of collections that were still limited, facilities and technology were still inadequate and lack of human resources. To minimize the obstacles in the collaboration that will be carried out next, the library has not made any efforts because it is still focused on inputting library materials into slims.